Is passive smoking associated with acute stress response? An observational real-world study - Qiongxuan Li; Rufang Gong; Qiao Wang; Hengyu Luan; Wei Lu; Xiaoguang Lu; Dongyao Li; Xiaoyong Sai (Frontiers in Public Health, 2026)
Background This study aimed to elucidate the potential association between passive smoking and the risk of post-traumatic stress disorder (PTSD) among high-stress rescue workers, including the magnitude of such an association, and to provide a evidence-based references for the early screening, prevention, and management of PTSD risk in high-stress rescue workers. Methods Using a cross-sectional design, the study distributed self-administered questionnaires to grassroots officers and soldiers. Data from 4,460 valid respondents were analyzed with logistic regression to quantify the association between passive smoking and positive screening under the Acute Stress Disorder (ASD) scale and PTSD Checklist for DSM-5 (PCL-5). Results Univariate analysis showed that passive smokers had a 2.509-fold higher risk of ASD compared with non-passive smokers (OR = 2.509, 95% CI = 1.621–3.883, p < 0.001), and a 3.298-fold higher risk of PTSD (OR = 3.298, 95% CI = 1.459–7.451, p = 0.004). Multivariate analysis revealed a significant association between passive smoking and ASD risk (OR = 1.990, 95% CI = 1.959–3.144, p = 0.003), Passive smoking showed a strong risk association with PTSD in the partially adjusted model (model 2: OR = 3.360, 95% CI = 1.473–7.665, p = 0.004; model 3: OR = 3.360, 95% CI = 1.473–7.665, p = 0.004), but this relationship was attenuated and became non-significant in the fully adjusted model (OR = 2.513, 95% CI = 0.9–5.151, p = 0.085). Stratified analysis among non-smokers showed that passive smokers had a 2.487-fold (OR = 2.487, 95% CI = 1.427–4.334, p = 0.001) higher risk of ASD than non-passive smokers in the univariate model. Further multivariate analysis indicated that, compared with non-smokers without passive smoking exposure, the risk of ASD was significantly elevated in both the exclusive passive smoking group (OR = 1.910, 95% CI = 1.071–3.408, p = 0.028) and the group with both active and passive smoking (OR = 2.389, 95% CI = 1.143–4.992, p = 0.021). Conclusions Significant correlations were identified between passive smoking and ASD/PTSD across the entire cohort. Specifically, among non-smokers, passive smoking exposure correlated significantly with elevated ASD risk, but its relationship with PTSD risk was indistinct. For the early screening of high-stress rescue populations, particular attention should be paid to documenting passive smoking exposure. Early intervention strategies need to prioritize reinforcing the enforcement of tobacco control policies and creating smoke-free settings, in order to mitigate the risk of ASD and PTSD linked to passive smoking exposure. Trial Registration Clinical research registration number: ChiCTR1900023441, registered on 27 May 2019.